A Proposed Model of Magnetic and Wind Energy to Generate Electricity: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Electricity is one of the most important things in our daily lives. However, most Filipinos cannotaccess or afford to possess electricity in their everyday lives. Most of the research stated thatmany Filipinos are affected by not being able to acquire electricity in their daily lives. Toaddress the aforementioned issue, the researchers conducted a study to find an alternativesource of energy to generate electricity. They used neodymium magnets and wind energy asthe alternative sources of electricity.The results of this study were highly acceptable as assessed by both electricians andmechanical engineers in terms of materials, while acceptable in terms of procedures,mechanisms, and presentation. It indicates the significant difference between theassessments of the two groups of respondents on the level of acceptability of magnetic andwind energy. The acquired mean of electricians is 3.15, while mechanical engineers have anacquired mean of 3.14. The variance for electricians is 0.334, while that for mechanicalengineers is 0.197. The t-computed value is 2.306, while the t-critical value is 0.196, with analpha level of 0.05 and a degree of freedom of 8. As a result, it accepts Ho.The researchers suggested finding a suitable mini fan blade for their model, using a strongermagnet and a large battery capacity, reducing the size of the box, and adding a cover on themini fan blade for safety handling.
Keywords: Mechanical engineering